Carl Gustav Johannsen, Staff-less Libraries. Innovative staffing design - Andruszko, Hanna (Biblioteka, 2019)
Recenzja. Carl Gustav Johannsen, Staff-less Libraries. Innovative staffing design, Cambridge, MA, Kidlington: Chandos Publishing 2017, s. 190 (Chandos Information Professional Series, 2052-210X). ISBN 978-0-08-101923-8 (print), 978-0-08-101924-5 (online)